2009
DOI: 10.1193/1.3148882
|View full text |Cite
|
Sign up to set email alerts
|

Shake Map Methodology for Intermediate-Depth Vrancea (Romania) Earthquakes

Abstract: We establish and test a shake map methodology for intermediate-depth Vrancea earthquakes, based on seismological information gathered in Romania during recent years. We use region-(azimuth-) dependent attenuation relations derived from stochastic simulations of ground motions using spectral models of Vrancea earthquakes. Both region boundaries and Fourier amplification spectra for the characterization of seismic site effects are based on several hundred weak, moderate and strong-motion records and macroseismic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The study has shown, based on the available ground motion recordings, a visible directional pattern for I JMA (Japan Meteorological Agency seismic intensity) [25], while in the case of RotD100 [24] the directional patterns (angles corresponding to RotD100) were less visible. Moreover, it has to be highlighted the fact that a significant number of ground motion prediction equations developed for the Vrancea intermediate depth seismic source employ azimuth-dependent coefficients [26][27][28][29][30]. On the other hand, the ground motion models of Vacareanu et al [31,32] had proposed different attenuation coefficients only for the backarc vs. forearc regions (both regions are defined with respect to the Carpathian Mountains).…”
Section: Assessment Of the Azimuthal Dependency Of Ground Motion Amplmentioning
confidence: 99%
“…The study has shown, based on the available ground motion recordings, a visible directional pattern for I JMA (Japan Meteorological Agency seismic intensity) [25], while in the case of RotD100 [24] the directional patterns (angles corresponding to RotD100) were less visible. Moreover, it has to be highlighted the fact that a significant number of ground motion prediction equations developed for the Vrancea intermediate depth seismic source employ azimuth-dependent coefficients [26][27][28][29][30]. On the other hand, the ground motion models of Vacareanu et al [31,32] had proposed different attenuation coefficients only for the backarc vs. forearc regions (both regions are defined with respect to the Carpathian Mountains).…”
Section: Assessment Of the Azimuthal Dependency Of Ground Motion Amplmentioning
confidence: 99%
“…Problems with the early warning for very large earthquakes have been identified earlier (Bose et al 2009) as finite earthquake source models have to be used, but were not implemented during the Tohoku earthquake in the JMA procedure. The meeting was, as shown in the video, interrupted by participants and immediately an orderly evacuation of the room took place (http://tremblingearth.…”
Section: Experience With Early Warning In Past Earthquakesmentioning
confidence: 99%
“…EEW systems are operational in select countries and regions, such as Japan [63,64], Taiwan [65][66][67], Mexico [54,68,69], South Korea [70] issue nationwide warnings, meaning alerts are broadcast to the entire public. While some countries issue region-specific warnings, as seismic vulnerability is localized to certain areas, such as Anatolia in Turkey [71,72], Southwest Iberia [73][74][75], Southern Italy [76][77][78], Vrancea-Romania [79][80][81], China [82,83], Chili [84], Costa Rica [85,86], Switzerland [87], Nicaragua [88], Israel [89,90] and United States of America [56,91]. As the advancement of the EEW system is pivotal for reducing seismic risk, enhancing its capacity to offer more lead time is equally imperative [92].…”
Section: Introductionmentioning
confidence: 99%